Diagnostic Exercise: Circling and Behavioral Changes in a Cat. (July 2015) - Faller, K.; Leach, J.; Gutierrez-Quintana, R.; Finck, M.; Hammond, G.; Penderis, J.; Marchesi, F.
A 4-year old spayed male domestic shorthair cat was presented with a history of circling and behavioral changes. Neurologic examination showed mild proprioceptive deficits. The lesion was localized in the forebrain, and magnetic resonance imaging revealed the presence of a large midline intracranial mass extending from the frontal lobe to the tentorial region of the brain. Euthanasia was elected due to poor prognosis. Histopathologic evaluation confirmed the presence of a mass composed by sheets and aggregates of large round/polygonal cells and multinucleate cells associated with deposits of cholesterol clefts, scattered hemorrhages and hemosiderin-laden macrophages. Immunohistochemistry showed that the round/polygonal cells and multinucleate cells were strongly positive for major histocompatibility complex class II antigen, variably positive for CD18, and occasionally positive for S100. Subsets of spindle cells showing variable expression of vimentin, S100, and neuron-specific enolase were also present. The final diagnosis was cholesterol granuloma. Differential diagnosis with meningioma is discussed.